The Use of Hypermedia Ispring Suite 9 in Teaching Reading Comprehension on Recount Text - Fitriyana Sakinah Daulay; Isli Iriani Indiah Br. Pane (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This research was aimed to know how to implement and why the iSpring Suite 9 implemented in teaching reading comprehension on recount text. iSpring Suite 9 is a software that can be integrated with Microsoft PowerPoint and this software can be used online or offline session for every students’ learning styles. This research using qualitative methods by using Descriptive Qualitative research. The sample of this research is the English teacher from SMPN 34 Medan grade VIII. The process of collecting data was conducted by using observation sheets, video and in-depth interview. The results of this research showed that the teacher was new in heard and also used this iSpring Suite 9 software and she learnt and took many information about this software until she can implemented it in the teaching and learning process in the classroom. The teacher used this software very well and said that this software was easy to use and this software can use for every students’ learning styles.Keywords: iSPring Suite 9, Reading Comprehension, Recount Text